Notch1 and Galectin-3 Modulate Cortical Reactive Astrocyte Response After Brain Injury - Ribeiro, Tais Novaki; Delgado-García, Lina Maria; Porcionatto, Marimelia A. (Frontiers in Cell and Developmental Biology, 2021)
After a brain lesion, highly specialized cortical astrocytes react, supporting the closure or replacement of the damaged tissue, but fail to regulate neural plasticity. Growing evidence indicates that repair response leads astrocytes to reprogram, acquiring a partially restricted regenerative phenotype in vivo and neural stem cells (NSC) hallmarks in vitro. However, the molecular factors involved in astrocyte reactivity, the reparative response, and their relation to adult neurogenesis are poorly understood and remain an area of intense investigation in regenerative medicine. In this context, we addressed the role of Notch1 signaling and the effect of Galectin-3 (Gal3) as underlying molecular candidates involved in cortical astrocyte response to injury. Notch signaling is part of a specific neurogenic microenvironment that maintains NSC and neural progenitors, and Gal3 has a preferential spatial distribution across the cortex and has a central role in the proliferative capacity of reactive astrocytes. We report that in vitro scratch-reactivated cortical astrocytes from C57Bl/6J neonatal mice present nuclear Notch1 intracellular domain (NICD1), indicating Notch1 activation. Colocalization analysis revealed a subpopulation of reactive astrocytes at the lesion border with colocalized NICD1/Jagged1 complexes compared with astrocytes located far from the border. Moreover, we found that Gal3 increased intracellularly, in contrast to its extracellular localization in non-reactive astrocytes, and NICD1/Gal3 pattern distribution shifted from diffuse to vesicular upon astrocyte reactivation. In vitro, Gal3–/– reactive astrocytes showed abolished Notch1 signaling at the lesion core. Notch1 receptor, its ligands (Jagged1 and Delta-like1), and Hes5 target gene were upregulated in C57Bl/6J reactive astrocytes, but not in Gal3–/– reactive astrocytes. Finally, we report that Gal3–/– mice submitted to a traumatic brain injury model in the somatosensory cortex presented a disrupted response characterized by the reduced number of GFAP reactive astrocytes, with smaller cell body perimeter and decreased NICD1 presence at the lesion core. These results suggest that Gal3 might be essential to the proper activation of Notch signaling, facilitating the cleavage of Notch1 and nuclear translocation of NICD1 into the nucleus of reactive cortical astrocytes. Additionally, we hypothesize that reactive astrocyte response could be dependent on Notch1/Jagged1-Hes5 signaling activation following brain injury.